2020
DOI: 10.3390/ijerph17249486
|View full text |Cite
|
Sign up to set email alerts
|

Determining Strategies for Constructing the Safety Supervision System by Considering Both Internal and External Safety Environments: A Case Study of X Group Corporation, China

Abstract: Safety supervision aims to safeguard the overall interests of the corporation, and ensure its safety production together with sustainable development. It is the key to reducing accident rates, and safeguarding employees’ safety and corporate property. The establishment of safety supervision system requires specify strategies. However, it is difficult to determine such strategies in an objective manner under complex environments. Therefore, first, this paper combined an external factor evaluation matrix (EFEM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Meanwhile, the QSPM (Qualitative Strategic Planning Matrix) is applied to determine the priority of the strategy to be selected based on the quantification of the strategy resulting from the SWOT analysis. The steps in the SWOT-QSPM method are as follows (Wang et al 2020;Budihardjo et al 2021).…”
Section: Analysis Of Alternative Strategymentioning
confidence: 99%
“…Meanwhile, the QSPM (Qualitative Strategic Planning Matrix) is applied to determine the priority of the strategy to be selected based on the quantification of the strategy resulting from the SWOT analysis. The steps in the SWOT-QSPM method are as follows (Wang et al 2020;Budihardjo et al 2021).…”
Section: Analysis Of Alternative Strategymentioning
confidence: 99%
“…Similarly, Ma and Zhao found that the increase of unit penalty cost can decrease the probability of workplace accidents [ 23 ]. Wang et al indicated that the establishment of a safety supervision system should consider both internal and external safety environments and that the most predominant strategies for establishing the safety supervision system lie in safety culture, organizational structure and safety performance evaluation [ 24 ]. In terms of research methods, Hausken and Zhuang adopted game theory to analyze the interactions between the enterprise’s safety effort and government’s safety supervision [ 9 , 10 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, studies on this issue are far from complete. Although some studies have explored optimal safety supervision decision-making [ 23 , 24 ], few studies have been conducted from a dynamic perspective in which the government adjusts its supervision strategies dynamically according to the real-time safety production status based on a high level of information transparency between stakeholders. Meanwhile, although some studies have proposed corresponding information systems to strengthen the information communication between the stakeholders [ 25 , 26 ], but these studies have usually paid attention to the technical aspects of developing an information system, and how the information system influences the stakeholders’ decision-making in the long-term safety supervision process remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Confined space operators are often in the first time and the first scene of the accident, it is certainly an inescapable duty for them to make decision, carry out safe self-and mutual-rescue, initiate an emergency response quickly, grasp the golden time and correct methods of rescue, prevent failure of rescue efforts through risk management [1] , supervision and management [9] , specific training [2] , and personal protective equipment [8] . Therefore, it is of great practical significance to study the failure factors of self-and mutual-rescue in confined space working accidents.…”
Section: Introductionmentioning
confidence: 99%